OpenedEyes - developing an information visualization framework using web standards and open web technologies - Almeida, Caio Sacramento de Britto; Apolinário Jr., Antônio L. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Extract knowledge from a dataset is not trivial. Information visualization shows up to help on this task by trying to optimize the user information gathering by using suitable graphical representations. There are some tools for this, but they are often focused on desktop, require advanced knowledge or use proprietary technologies. The proposal of this work is to present OPENEDEYES, a JavaScript framework that uses web standards to implement interactive information visualization modules to be run in a web browser. From the framework core, a case study was built based on a real dataset for an empiric framework evaluation. Traditional and new techniques were implemented confirming the flexibility and extensibility of the framework.